Per-phase spatial correlated damage models of UD fibre reinforced composites using mean-field homogenisation; applications to notched laminate failure and yarn failure of plain woven composites. (December 2021) - Wu, Ling; Zhang, Tianyu; Maillard, Etienne; Adam, Laurent; Martiny, Philippe; Noels, Ludovic
Highlights: A phase-field micro-mechanical model for fibre bundle is formulated. This micro-mechanical model is embedded in a semi-analytical homogenisation scheme. Mesh-independence and energy release rate consistency for fibre bundles are ensured. Matrix cracking and fibre-matrix debonding are modelled by a matrix damage variable. The framework is applied to model UD laminates and woven unit-cell failure. Abstract: A micro-mechanical model for fibre bundle failure is formulated following a phase-field approach and is embedded in a semi-analytical homogenisation scheme. In particular mesh-independence and consistency of energy release rate for fibre bundles embedded in a matrix phase are ensured for fibre dominated failure. Besides, the matrix cracking and fibre-matrix interface debonding are modelled through the evolution of the matrix damage variable framed in an implicit non-local form. Considering the material parameters of both fibre and epoxy matrix phases identified from manufacturer data sheets, it is shown that the failure strength of a ply loaded along the longitudinal direction is in agreement with the reported values. Finally, the multi-damage homogenisation framework is applied to model, on the one hand, the failure of a notched laminate, in which case the failure modes are observed to be in good agreement with experiments, and, on the other hand, the failure of yarns in a plain woven composite unit-cell under uni-axial tension.